Analysis of Factors Affecting the Event of Diarrhea in Infants Age 0 to 2 Years - Antika Maulida Rahayu; Ismarwati Ismarwati (Universitas 'Aisyiyah Yogyakarta, 2020)
Diarrhea is the number 2 cause of death among children under five in the world, number 3 in infants, and number 5 for all ages. There are several factors that influence the occurrence of diarrhea in infants apart from infectious factors (bacterial infections, viral infections, parasitic infections, parenteral infections). Other contributing factors are attainment of breastfeeding, food factors, and water sources used daily. The aim of this literature review is to analyze the factors that influence the incidence of diarrhea in infants aged 0 to 2 years. a process using the search stage to conduct a literature review. A search of relevant databases as well as literature and reference lists of included studies was carried out. An analysis of 10 journals conducted by researchers showed that infants aged 10 months who were fully breastfed when associated with diarrhea had lower scores (OR = 0.59, 95% CI 0.43-0.82), while children -children who received food and candy or milk were associated with an increased prevalence of diarrhea, namely (OR = 1.64, 95% CI 1.22-2.22 and OR = 1.67, 95% CI 1.21-2.30 ). And 2.58 times higher in homes with damaged water filters (OR = 2.58, 95% CI 0.1, 10.1) compared to homes with working water filters. 15% of families with good water filters reported diarrhea, while 31% of families with damaged water filters reported diarrhea. Exclusive breastfeeding for up to 6 months can reduce the risk of diarrhea in infants.